Linking pavement condition index and international roughness index: Insights from rural roads in Myanmar - Nandar Tun; Kyaing Kyaing; Moe Thet Thet Aye (Researcher and Lecturer Society, 2024)
There is no comprehensive understanding of the relationship between the Pavement Condition Index (PCI) and the International Roughness Index (PCI) in rural road in Myanmar, which is important for developing effective and efficient maintenance strategies. This study evaluated the relationship between the Pavement Condition Index (PCI) and the International Roughness Index (IRI) in flexible rural roads in Myanmar. The aim of this study is to examine how these two key variables correlate and how their relationship can optimize maintenance strategies. Data were collected from ten flexible rural roads in Shan State over 3 years, divided into 25-meter subsections per road. The analysis showed that PCI and IRI have a strong negative linear relationship, with an R-value (0.748) and an R-squared value (0.559). The study demonstrates the significance of IRI as a key predictor of pavement condition by showing that IRI can account for 55.9% of the variability in PCI. The study concluded that increasing IRI leads to a fall in the PCI, suggesting poorer pavement conditions. These findings emphasize incorporating IRI measurements in pavement maintenance planning to ensure smoother and safer roads, especially in rural areas. The results contribute to more effective and sustainable maintenance practices, optimizing resource allocation and extending pavement lifespan.